A novel hybrid approach to the repair of flank hernias - Brendan P Chou; Karalyn Bentley; Karl A LeBlanc (International Journal of Abdominal Wall and Hernia Surgery, 2022)
Background: Flank hernias are uncommon and challenging to repair. Discussion of flank hernia repair is scarce in the literature. We present a novel approach to repair flank incisional, traumatic, and denervation hernias with a “hybrid” approach using an open repair in conjunction with the robotic platform for laparoscopic intraperitoneal mesh fixation. Materials and Methods: A retrospective analysis was conducted on all patients who received a “hybrid” repair from April 2014 through January 2020 by a single surgeon. Patient and hernia characteristics, operative techniques, and outcomes were evaluated. Each patient underwent a similar operation with an intraperitoneal mesh as well as an onlay mesh. Minor technique changes including quilting and wound vac placement were developed and compared. Results: Twenty-five patients were included in the study. Outcomes analyzed included wound infection (8.0%), seroma formation (16.0%), hematoma formation (12.0%), mesh infection (0.0%), weight gain (16.0%), hernia recurrence (4.0%), reoperation (12.0%), and chronic pain (25.0%). Compared to the drain placement group, quilting of the subcutaneous tissue was more likely to result in seroma (17.6% vs. 12.5%, P = 0.618) and hematoma (17.6% vs. 0.0%, P = 0.296). Use of negative pressure incisional wound vac did not impact the incidence of wound infection (12.5% vs. 6.2%, P = 0.565), seroma (12.5% vs. 17.6%, P = 0.618), or hematoma formation (12.5% vs. 11.8%, P = 0.704). Conclusion: The “hybrid” repair represents a novel approach to flank hernias. Improved visualization of the intraperitoneal portions of the operation using the robotic platform allows for accurate mesh fixation. In experienced hands, this approach provides safe and satisfactory outcomes similar to a purely open repair.